Selective C-methylation of phenol with methanol over transition metals modified mesoporous ceria catalysts - K.J, Rose Philo; S, Sugunan (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
The demand for selective catalysts with larger molecular dimensions led to the discovery of mesoporous catalytic materials. We report herein the development of an environmentally friendly process for C-methylation of phenol derivatives with methanol using mesoporous ceria modified with transition metals.Â  Selective C-methylation of phenol, has been investigated over transition metals loaded mesoporous ceria. Catalyst reaction rates at various reaction parameters were also investigated. 98% selectivity for ortho-alkylated products (o-cresol and 2, 6-xylenol) was obtained. The reaction is proved to be first order with phenol conversion. The frequency factor A and the activation energy Ea were also evaluated with (CeFe10%) catalyst.